Numerical Analysis of Droplet Impact on Liquid Film with Different Surface Structures - Y. Li; Y. Lou; Z. He; M. Liu (Journal of Applied Fluid Mechanics)
The collision of droplets with a liquid film is a common occurrence in daily generation . This study uses the CLSVOF approach to analyze a droplet's effect on a liquid film with various trapezoidal surface structures. It analyzes the spray morphology, velocity field, pressure distribution, and the characteristic arguments of the crown and cavity under different trapezoidal widths, heights, and hypotenuse lengths. The findings suggested that growing the height promotes spatter, the collision of droplet with liquid film forms mushroom-shaped velocity region and a zero-velocity region, while generating symmetrical vortices. The area above the trapezoid is identified as a high-pressure region, with its size increasing as the hypotenuse length and trapezoidal width rise and decreasing as the height increases. Three localized high-pressure regions are observed during the impact procedure, and the crown diameter grows with greater height. The bottom diameter of the cavity is influenced by the height, width, and hypotenuse length, with the hypotenuse length exerting the most significant effect. This study provides a theoretical foundation for applying droplet and liquid film collisions.